2021
DOI: 10.1016/j.eclinm.2021.100936
|View full text |Cite
|
Sign up to set email alerts
|

The influence of selection bias on identifying an association between allergy medication use and SARS-CoV-2 infection

Abstract: Background: Medications to prevent and treat SARS-CoV-2 infection are needed to complement emerging vaccinations. Recent in vitro and electronic health record (EHR) studies suggested that certain allergy medications could prevent SARS-CoV-2 infection. We sought to carefully examine the potential selection bias associated with utilizing EHRs in these settings. Methods: We analyzed associations of three allergy medications (cetirizine, diphenhydramine or hydroxyzine) with testing negative for SARS-CoV-2, measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…There is also likely selection bias, as UC patients with cancer may have undergone more tests than those without cancer due to mandated asymptomatic testing prior to infusions, radiation therapy, and surgeries, as had been instituted in some UC medical centers. A similar selection bias was found to potentially explain the association between allergy medication use and decreased SARS‐CoV‐2 infection 21 . We found that patients receiving systemic therapy were also less likely to test positive, perhaps for similar reasons.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There is also likely selection bias, as UC patients with cancer may have undergone more tests than those without cancer due to mandated asymptomatic testing prior to infusions, radiation therapy, and surgeries, as had been instituted in some UC medical centers. A similar selection bias was found to potentially explain the association between allergy medication use and decreased SARS‐CoV‐2 infection 21 . We found that patients receiving systemic therapy were also less likely to test positive, perhaps for similar reasons.…”
Section: Discussionsupporting
confidence: 74%
“…A similar selection bias was found to potentially explain the association between allergy medication use and decreased SARS‐CoV‐2 infection. 21 We found that patients receiving systemic therapy were also less likely to test positive, perhaps for similar reasons. Therefore, these findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 62%
“…159 ). For example, patients using allergy medications were more likely to be tested for COVID-19, which leads to an artificially lower rate of positive tests, and an apparent protective effect among those tested-probably due to selection bias 160 . Importantly, selection bias can result in AI models trained on a sample that differs considerably from the general population 161 , thus hurting these models at inference time 162 .…”
Section: Masked (And Shifted) Targetmentioning
confidence: 99%
“…Selection bias was cautioned, citing the observation that increasing age and public insurance were associated with a higher adjusted odds of test negativity, while being Black or Hispanic was significantly associated with test positivity. (Thompson et al, 2021).…”
Section: Antihistaminementioning
confidence: 99%